Exchange Rate Shocks and Assessing the Prospect of a Common Currency Union in East Asia - Salim, Ruhul; Kabir, M.S. (World Business Institute Australia, 2012)
This article investigates the role of real exchange rates on the ASEAN integration process by using a VAR model estimated for each ASEAN member with data for 1960 through 2010. Empirical results show that there is substantial heterogeneity among the ASEAN economies and demonstrate no significant impact of real exchange rate shocks on ASEAN trade. The study suggests that the ASEAN common currency would not provide a trade benefits additional to those from the ongoing integration process.